Humic acid induces the endothelial nitric oxide synthase phosphorylation at Ser1177 and Thr495 Via Hsp90α and Hsp90β upregulation in human umbilical vein endothelial cells. Issue 2 (8th July 2013) - Tanaka, Masato; Miyajima, Miki; Hishioka, Naoko; Nishimura, Ryo; Kihara, Yusuke; Hosokawa, Toshiyuki; Kurasaki, Masaaki; Tanaka, Shunitz; Saito, Takeshi
ABSTRACT: Humic acid (HA) has been implicated as a contributory factor for blackfoot disease, which is an endemic peripheral vascular disease. We investigated the effect of HA on the regulation of endothelial nitric oxide (NO) synthase (eNOS) in human umbilical vein endothelial cells (HUVECs) to evaluate the involvement of eNOS and related factors in peripheral vascular impairment with HA exposure. Treatment of HUVECs with HA induced upregulation of eNOS. This result coincides with those of previous studies. Furthermore this is the first study to report that HA induces upregulation of heat shock protein (Hsp)90α, Hsp90β, eNOS phosphorylation at Ser1177, and eNOS phosphorylation at Thr495, as compared to that in the control. In contrast, treatment with BAPTA, an intracellular Ca 2+ chelator, inhibited upregulation of these proteins induced by HA. This study demonstrates that HA treatment leads to increases in both Hsp90α and Hsp90β proteins and indicates that Hsp90α leads to eNOS phosphorylation at Ser1177 and that Hsp90β leads to eNOS phosphorylation at Thr495, respectively. Upregulation of eNOS, Hsp90α, and Hsp90β in HUVECs is regulated by intracellular Ca 2+ accumulation induced by HA. These results suggest that upregulation of eNOS phosphorylation at Ser1177 and eNOS phosphorylation at Thr495 produce NO and superoxide anions, respectively, resulting in generation of peroxynitrite, which causes impairment of vascular endothelial cells. © 2013 Wiley Periodicals, Inc. Environ Toxicol 30: 223–231, 2015.